Illuminating Ugarit: an iconographical study of the Egyptian influence on Ugarit during the Late Bronze Age (ca. 1600-1150 BCE) - O'Connor, Peter (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.